Sistem Pakar Penentuan Gizi Makanan Bagi Pasien yang Opname Menggunakan Metode Fuzzy - Tsukamoto [Studi Kasus Klinik dan Rumah Sakit Ibnu Sina Dampit, Malang] - Rizqi Addin Arfiansyah; Edy Santoso; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Nutrition is everyone's requirement. Everyone needs a good nutritional intake. A healthy body certainly needs nutrition well. Especially with the condition of ill certainly require more nutrition in accordance with his illness. In this study at the clinic and hospital Ibn Sina Dampit there are patients who are hospitalized who need nutritional intake. In this case there is already a search method of required nutrient levels issued by the health department. With the name rumua AMB (basal metabolic rate). By using the formula AMB can know a number of calories needed. The authors discussed using Fuzzy Tsukamoto method as a reference for the determination of nutritional foods that work with experts to create an expert system of nutritional determination of food for patients who hospitalization. Here the author why using the method of Fuzzy tsukamoto due to Tsukamoto method method is stronger than Fuzzy Mamdhani or Fuzzy Tsugeno method. In the fuzzy inference system there are several methods, such as mamdani method, sugeno method, tsukamoto method, but in this thesis use tsukamoto method because tsukamoto method is one method of fuzzy logic, which is used to calculate the decision result (z) of a disease. It represents an input to the output space with an IF- THEN-shaped rule with a membership function that is represented by the state space of a sample and the resulting end result is a decision value as a weighted average (z). And produce accuracy with 90% accuracy percentage based on data used